Incidence of lower limb injuries in children and adolescents practicing combat sports: a systematic review - Fernando de Lima; Renato Locks; Gilberto Melo; Francisco Rosa Neto (Sport Sciences for Health, 2026)
Abstract Purpose To assess the incidence rate of lower limb injuries in children and adolescents practicing combat sports. Methods Five databases (Embase, PubMed, SCOPUS, SPORTDiscus, and Web of Science) were searched, encompassing articles published up to February 04, 2026. Studies investigating individuals ≤19 years old practicing any combat sport were considered eligible. Information extracted from included articles comprised key elements, such as sample size, participants’ age and sex, exposure measure, sport characteristics, use of protective gear, injury types, and incidence rates. Injury incidence rates (IR) were estimated and reported per 1000 athlete exposure (AE). Results From 1951 records found, 148 were assessed for eligibility, and 30 included for analysis. Of these, most studies investigated Wrestling ( n =18), followed by Taekwondo ( n =5), Judo ( n =4), and Karate ( n =3). Due to overlapping samples, only 12 studies were further assessed by presenting individual study estimates in forest plots. The IR for grappling sports ranged from 0.07 to 3.85 per 1000 AE, including Wrestling (0.07 to 1.86) and Judo (3.85). For striking sports, the IR ranged from 4.60 to 23.66 per 1,000 AE, including Karate (5.00 to 12.74) and Taekwondo (4.60 to 23.66). The most commonly reported injured body parts were the foot/toes, knees, and ankles. Conclusion Within the limitations of this systematic review, children and adolescents practicing combat sports presented IRs ranging from 0.07 to 23.66 per 1,000 AE considering lower limb injuries, with higher IRs observed in studies assessing striking sports compared to grappling sports.